MEASURES TO PREVENT EXPLOSION AND FIRE HAZARDS IN THE OIL AND GAS INDUSTRY - Semchuk, Ya. M.; Kryvenko, G. M.; Hrytsuliak, H. М.; Kryvenko, О. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
One of the main dangers of the oil and gas industry is a sufficiently high level of risk of explosions and fires caused by the presence in the processes of extraction, transportation and storage of significant masses of hydrocarbons, which under certain conditions can create explosive and fire-hazardous concentrations of flammable gases or vapors. To prevent the occurrence of such conditions, safety regulations provide for a number of design and planning standards and means of a technical, technological and organizational nature. Ventilation of explosion-hazardous premises plays an important role in preventing the occurrence of dangerous situations. One of the important purposes of ventilation is to prevent the formation of explosive concentrations of flammable gases, vapors or dust. Therefore, the prevention of explosion and fire hazards in the oil and gas industry is relevant. The purpose of the work is to clarify the methodology for determining indicators that regulate explosion and fire hazards at fuel and energy complex facilities. To achieve the set goal, the following tasks were solved: substantiation of the definition of indicators regulating explosion and fire hazards at oil and gas facilities and measures to prevent explosion and fire hazards. Due to certain terminological and substantive changes that have occurred during the formation of the regulatory framework for labor protection in recent decades, the definition of the lower concentration limit of explosion and the lower concentration limit of flame propagation, which regulate explosion and fire hazards, requires clarification. Measures to prevent explosion and fire hazards within working areas that do not have spatial restrictions are based primarily on controlling air gas contamination in order to promptly detect dangerous concentrations and prevent the presence of sources of ignition (ignition) of gas-air mixtures in dangerous areas (principles of "concentration and localization"). Measures for preventing explosion and fire hazards within working areas that do not have spatial restrictions are presented, and a refined methodology for determining indicators that regulate explosion and fire hazards at fuel and energy complex facilities is provided. Keywords: Exhaust emergency ventilation, concentration, probability of mixture non-ignition, degree of mixture heterogeneity, explosive situation.